Migration-tracking integrated phylogeography supports long-distance dispersal-driven divergence for a migratory bird species in the Japanese archipelago - Aoki, Daisuke; Takagi, Masaoki (Dryad, 2019)
Previous phylogeographic studies of migratory bird species have not
discriminated long-distance dispersal (LDD) from vicariant
speciation in their diversification process. We conducted an integrative
phylogeographic approach to test the LDD hypothesis, which predicts that a
Japanese migratory bird subspecies diverged from a population in the
coastal region of the East China Sea (CRECS) via LDD over the East China
Sea (ECS). We used the Brown Shrike as a model species, and we conducted
molecular phylogenetics, species distribution models (SDMs) and migration
tracking. We assessed whether the LDD hypothesis is applicable to the
divergence history of the Japanese subspecies of the Brown Shrike. The
datasets include three zipped files, namely DataS1.zip, DataS2.zip, and
DataS3.zip. See the READ ME (AOKI_et_al_2021_DATASET_README.txt) for how
each of the folder and files contained in them can be used to reproduce
our results. DataS1.zip inlcudes an xml file to conduct the BEAST
analysis. Molecular data, which include nucleotide sequences
obtained for cytochrome b (cytb), cytochrome oxidase c subunit I (COI),
myoglobin intron-2 (MB) and transforming growth factor beta 2 intron-5
(TGFb2), have been all reposited to DDBJ international nucleotide sequence
database, and accession numbers have been already given to them. Accession
numbers are provided in the appendix attached to the main manuscript.
DataS2.zip includes several data that are related to produce occurrence
data of the Brown Shrike used in the analysis and an R code to
reproduce the SDMs. Explanatory climatic variables are all available at
WorldClim v.1.4 (Hijmans et al., 2005), which are processed in the R code.
DataS3.zip includes migratory route analyses using light-level geolocator
data are available as the original light-level data and R codes.
Sensitivity analyses were also conducted in these analyses, but their
codes and results are seperately provided here.
See the READ ME (AOKI_et_al_2021_DATASET_README.txt) for how each of the
folder and files contained in them can be used to reproduce our results.
Keywords: Brown Shrike; Lanius cristatus; light-level geolocator